Optimization of embryonic thermal programming confirms increased liver fattening in mule ducks and changes in lipid metabolism - Andrieux, C.; Marchand, M.; Larroquet, L.; Veron, V.; Biasutti, S.; Morisson, M.; Coustham, V.; Panserat, S.; Houssier, M. (Frontiers in Physiology, 2023)
Embryonic thermal manipulations (TM) can induce hepatic metabolic programming increasing liver weight and liver fattening after overfeeding in mule ducks. However, a decrease in hatchability and foie gras quality was also observed, suggesting that this technique needs to be optimized. Here, we tested a new thermal manipulation condition determined with the objective of avoiding negative impacts while maintaining or improving liver properties. The eggs of the control group were incubated at 37.6°C during the whole incubation period while those of the experimental group (TM group) were incubated at 39.3°C 16h/24h from the 11th day of incubation to the 21st. After hatching, all the animals were fed and raised under the same conditions until the age of 12 weeks. At this stage, one part of the animals was overfed and then slaughtered 2h (to measure rapid changes in metabolism) or 10h after the last meal (to obtain the best technological yields), while the other part was not overfed and was slaughtered 2h after the last meal, at the same age. An 8 % increase in foie gras production was measured in the TM group compared to the control group without alteration of quality, confirming the successful optimization of the metabolic programming. Interestingly, measurements performed 2h or 10h after the last meal allowed us to confirm a potential delay in metabolic processes involved in liver fattening in programmed animals, evidenced by differences in lipid composition (saturated and poly unsaturated fatty acids) and hepatic gene expression (lipid and carbohydrate metabolisms). This study therefore validates the optimization of metabolic programming by embryonic thermal manipulation for duck liver fattening but also opens new exploratory ways of the mechanisms involved.